A Liquid Metal Based Multimodal Sensor and Haptic Feedback Device for Thermal and Tactile Sensation Generation in Virtual Reality. (16th December 2020) - Oh, Jinhyeok; Kim, Suin; Lee, Sangyeop; Jeong, Seongmin; Ko, Seung Hwan; Bae, Joonbum
Abstract: Virtual reality (VR) has been widely used for training, gaming, and entertainment, and the value of VR is continually increasing as a contact‐free technology. For an immersive VR experience, measuring finger movements and providing appropriate feedback to the hand are as important as visual information, given the necessity of the hands for activities in daily life. Thus, a hand‐worn VR device with motion sensors and haptic feedback is desirable. In this paper, a multimodal sensing and feedback glove is developed with soft, stretchable, lightweight, and compact sensor and heater sheets manufactured by direct ink writing (DIW) of liquid metal, eutectic gallium‐indium (eGaIn). In the sensor sheet, ten sensors and three vibrators are embedded to measure finger movements and provide vibro‐haptic feedback. The other heater sheet provides thermo‐haptic sensation in accurate and rapid manner via model‐based feedback control even under stretched conditions. The multimodal sensing and feedback glove allows users to feel the contact status and discriminate materials with different temperature. Performance of the proposed multimodal glove is verified under VR environments including touching and pushing two blocks of different materials and grabbing a heated metal ball submerged in hot water. Abstract : A multimodal sensing and feedback glove, which can measure finger movements and provide vibro‐haptic and thermo‐haptic feedback simultaneously, is developed with soft, stretchable, lightweight, and compact sheets manufactured by direct ink writing of liquid metal, eutectic gallium‐indium. The resulting glove allows users to feel the contact status and different temperature under various virtual reality environments.